KANDUNGAN HARMONISA PADA LAMPU HEMAT ENERGI - Wahri Sunanda (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2014)
Harmonic is one of sinusoidal components, one wave period from which having multiple frequency of its fundamental frequency one, leading to electrical power quality problems. Harmonic distortion in term of voltage and current ones, generally is due to non linier impedance. Energy saving lamp is one of example of it. This research was done by performing studies in harmonic voltage and harmonic current from four different brands of energy saving lamp having power rating of 8 watt, 16 watt, and 20 watt and uses IEEE Standard of 519-1992 as a reference in determining maximum limitation voltage and current harmonics. The result of the tests were showed that total harmonic distortion (THD) voltage at each different brand of energy saving lamp having power rating of 8 watt, 16 watt, and 20 watt did not exceed the IEEE 519-1992 maximum limitation of 5%. While total harmonic distortion (THD) current at each different brand of energy saving lamp having power rating of 8 watt, 16 watt, and 20 watt had exceed result range exceeding 71,2%.